MHD Boundary Layer Flow of a Nanofluid Over an Exponentially Stretching Sheet in the Presence of Radiation. Issue 4 (3rd October 2013) - Loganathan, P.; Vimala, C.
<x xml:space="preserve">Abstract</x> Effects of thermal radiation on the steady laminar magnetohydrodynamic boundary layer flow of a nanofluid over an exponentially stretching sheet is studied theoretically. The governing boundary layer equations of the problem are formulated and transformed into ordinary differential equations, using a similarity transformation. The resulting ordinary differential equations are solved numerically by the shooting method. The effects of the parameters, namely, the magnetic parameter M, radiation parameter NR, and the solid volume fraction parameter ϕ, are discussed and presented in detail. Different types of nanoparticles namely, Cu, Ag, Al2O3, and TiO2 with the base fluid water, are studied. It is found that the nanoparticles with low thermal conductivity, TiO2 have better enhancement on heat transfer, compared to Cu, Ag, and Al2O3. © 2013 Wiley Periodicals, Inc. Heat Trans Asian Res, 43(4): 321–331, 2014; Published online 3 October 2013 in Wiley Online Library (wileyonlinelibrary.com/journal/htj). DOI 10.1002/htj.21077